Analisis Efisiensi Usaha Pande Besi dengan Metode Data Envelopment Analysis (DEA) - Wunu, Dedi Hiwa; Kelen, Lusianus Heronimus Sinyo (AKSIOMA : Jurnal Manajemen, 2023)
This study aims to analyze the efficiency of the pande besi business using the Data Envelopment Analysis (DEA) method (a study on blacksmith businesses in Kota Waingapu District, East Sumba Regency). In this study, the method used is the descriptive quantitative method. The type of data used in this research is primary data. The data collection method used in this study, namely interviews, is to collect relevant data obtained from the owner of the blacksmith business in the District of Waingapu City. This research uses an analysis tool, Data Envelopment Analysis (DEA). The software used for research is DEAP version 2.1. Variables that affect output include production factors that affect production. Based on the results of the research, the authors have found that of the 6 respondents in the blacksmith business, the product units that did not achieve efficiency were traditional machetes, knives, and sickles, the sources that caused inefficiency in each product unit in the blacksmith business came from the less optimal use of variable input and output. Turning inefficient businesses into efficient ones can be done by adjusting the actual values of the inefficient input and output variables to the target values recommended by the DEA.